A Solution for Inputting Vietnamese Handwritten Text on Tablet PC - Nguyen , Đăng Quang; Dinh , Công Đoan (Journal of Technical Education Science, 2021)
TabletPCs are quite familiar nowadays. Vietnamese handwriting recognition on Tablet PC however has not been supported so far. We developed a solution to input Vietnamese handwritten text on TabletPC by using the Microsoft Windows TabletPC API. The solution was proposed to replace the default TabletPC Input Panel (TIP) whenever users want to enter Vietnamese text on slate TabletPC or convertible TabletPC in slate mode.